Interactions Between Gut Microbiota and Acute Restraint Stress in Peripheral Structures of the Hypothalamic–Pituitary–Adrenal Axis and the Intestine of Male Mice - Vagnerová, Karla; Vodička, Martin; Hermanová, Petra; Ergang, Peter; Šrůtková, Dagmar; Klusoňová, Petra; Balounová, Kateřina; Hudcovic, Tomáš; Pácha, Jiří (Frontiers in Immunology, 2019)
The gut microbiota play an important role in shaping brain functions and behavior, including the activity of the hypothalamus-pituitary-adrenocortical (HPA) axis. However, little is known about the effect of the microbiota on the distinct structures (hypothalamus, pituitary, adrenals) of the HPA axis. In the present study, we analyzed the influence of the microbiota on acute restraint stress (ARS) response in the pituitary, adrenal gland and intestine, an organ of extra-adrenal glucocorticoid synthesis. Using specific pathogen-free (SPF) and germ-free (GF) male BALB/c mice, we showed that the plasma corticosterone response to ARS was higher in GF than in SPF mice. In the pituitary, stress downregulated the expression of the gene encoding CRH receptor type 1 (Crhr1), upregulated the expression of the Fkbp5 gene regulating glucocorticoid receptor sensitivity and did not affect the expression of the proopiomelanocortin (Pomc) and glucocorticoid receptor (Gr) genes. In contrast, the microbiota downregulated the expression of pituitary Pomc and Crhr1 but had no effect on Fkbp5 and Gr. In the adrenals, the steroidogenic pathway was strongly stimulated by ARS at the level of the steroidogenic transcriptional regulator Sf-1 and cholesterol transporter Star, but the effect of the microbiota on adrenal steroidogenesis was weak and was significantly detected only at the level of gene Cyp11a1, encoding the cholesterol side-chain cleavage enzyme. Unlike adrenal Sf-1, the expression of the gene Lrh-1, which encodes the crucial transcriptional regulator of intestinal steroidogenesis, was modulated by the microbiota and ARS and this effect differed between the ileum and colon. The findings demonstrate that gut microbiota have an impact on the response of the pituitary, adrenals and intestine to ARS and that the interaction between stress and the microbiota during activation of glucocorticoid steroidogenesis differs between organs. The results suggest that downregulated expression of pituitary Pomc and Crhr1 in SPF animals might be an important factor in the exaggerated HPA response of GF mice to stress.al